Synthesis of Large Pyrene-Fused Azaacenes - Ji, Jason D.; Zhu, Lei; Klug, Christopher L.; Smith, Mark D.; Miao, Shaobin (Synthesis, 2015)
The facile synthesis of pyrene-fused tetraazaheptacene and tetraazaoctacene is reported. The new compounds are fully soluble in common organic solvents. The absorption spectra of both compounds reveal that they have low energy gaps. The structure of tetraazaoctacene was confirmed by single crystal X-ray diffraction analysis.
Keywords: azaacenes; crystal structures; electronic materials; pyrene; solubility